Desinformación: aproximación conceptual, riesgos y remedios - Astudillo Muñoz, Jorge (2024)
The current work seeks to offer a general reflection on the phenomenon of misinformation in the digital age in order to raise awarenessabout the risks it poses to the normal development of democratic processes. Furthermore, it aims to emphasize the need to approach misinformation from various perspectives, in harmony with full respect for freedom of expression. The study intends to provide tools that allow the clear identification of misinformation, to point out some thoughts regarding the purposes that underlie the act of misinforming and to review the main stages of the misinformation process. It also strives to offer a more comprehensive understanding of the concept of misinformation, by proposing a distinction and identifying the connections between this activity and the communicative phenomenon of fake news. Later on, the analysis concentrates on the effects that misinformation has on democracy and the respect for human rights, particularly within the context of modern societies characterized by the use of ICTs. Lastly, a brief overview is presented of some of the tools that could be considered to confront misinformation, although the study will not delve into each of these remedies due to its length constraints.